Educational interventions to mitigate misinformation among university students: A scoping review - Etesse, Manuel (2025)
Introduction: Information disorders represent a growing threat to social cohesion, public health, and democratic systems. Media literacy in higher education emerges as a key strategy to mitigate their impact, although its implementation poses theoretical and methodological challenges. Objective: This study aimed to analyze the empirical production politeracy interventions targeting university students, identifying the theoretical frameworks underpinning them, their implementation and methodological characteristics, and the reported effectiveness of these strategies in mitigating misinformation in students. Method: A scoping review was conducted following the PRISMA-ScR model. A total of 27 articles published between 2012 and 2024 were analyzed, all documenting educational interventions implemented in university settings across various regions. Results: The findings reveal a geographic concentration in the United States and a surge in research activity since 2020. Interventions focus on strengthening critical thinking and the mindful use of information, with prominent approaches including inoculation theory and educational video games. Quantitative studies dominate, particularly observational and experimental designs, although only half included over 300 participants. Several studies lack validated instruments and rigorous sample size estimations. Discussion: The analysis reveals a fragmented theoretical landscape that hinders comparability and field consolidation. The study recommends the development of standardized methodological frameworks, interdisciplinary approaches, and the design of context-aware, sustained, and culturally relevant interventions. These actions are essential to enhance the effectiveness and sustainability of educational strategies in addressing misinformation within higher education contexts.